The development of the national character grand design through the “Smart Mobile Civic” application as an evaluation of civic education learning - Trisiana, Anita; Farida Sari, Ama; Azizah, Nur (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
The digital learning revolution can be implemented through various models and media, one of which is the development of the Project Citizen model, realised in an application called “SMART MOBILE CIVIC”. It can be stated, addressing the challenge of shaping a comprehensive grand design for national character requires ensuring that character education in higher education adapts to and remains relevant within the evolving landscape of digital era learning transformations. In this context, the present research seeks to formulate a policy framework for strengthening national character by employing the “SMART MOBILE CIVIC” application as an evaluative medium for the Civic Education learning process. The novelty of the socio-cultural science and technology product lies in the 'SMART MOBILE CIVIC' application, a computer/Android-based program designed to integrate national character values and measure digital literacy skills through the 'Character Survey' within the non-cognitive learning aspects of Civic Education.  Data collection was conducted using several methods, including field observation (participant observation), focus group discussions (FGD), in-depth interviews, documentary studies, and questionnaires. Data analysis used in qualitative research is based on the Interactive Analysis Model. According to this model, in data collection, researchers continuously reduce and present data until a conclusion is drawn. The results of the study show that, first, the implementation of national character integration through the “Smart Mobile Civic” application serves as a conceptual and operational reference for the development, implementation, and assessment of grand design at every educational path and level.  The character configuration, in the context of the totality of psychological and socio-cultural processes, is grouped into Spiritual and Emotional Development, Intellectual Development, Physical and Kinesthetic Development, and Affective and Creative Development. Second, the development and implementation of character education need to be carried out by referring to the grand design used as an evaluation of civic education learning through 7 (seven) systematic steps that refer to the measurement of global citizenship competencies.